Livelihoods in Sudan amid armed conflict: Evidence from a national rural household survey - International Food Policy Research Institute; United Nations Development Programme; Kirui, Oliver K.; Ahmed, Mosab O. M.; Siddig, Khalid; Taffesse, Alemayehu Seyoum; Abushama, Hala; Dorosh, Paul A.; Fakih, Ali; Terefe, Fekadu; Nohra, Nada; AlAzzawi, Shireen; et al. (International Food Policy Research Institute, 2024)
Analysis of a comprehensive survey of Sudanese rural households conducted from November 2023 to January 2024 by IFPRI and UNDP reveals significant socioeconomic impacts of the ongoing armed conflict on the Sudanese population, underscoring the need for immediate and targeted policy and programmatic interventions. The conflict has severely disrupted rural household incomes and exacerbated existing vulnerabilities related to their housing and access to infrastructure and services. Most households live in inadequate housing conditions, with disparities in access to water, electricity, and sanitation services posing additional challenges. Rural households’ low access to assets, including agricultural land, further complicates their livelihoods.